Corpus-based approaches to language description for specialized academic writing. (22nd December 2014) - Flowerdew, John
Abstract : Language description is a fundamental requirement for second language (L2) syllabus design. The greatest advances in language description in recent decades have been done with the help of electronic corpora. Such language description is the theme of this article. The article first introduces some basic concepts and principles in corpus research. It then reviews some recent corpus studies of relevance to the teaching of English for specific purposes (ESP) writing. The speech focuses on four different types of corpora: expert professional corpora, expert student corpora, L2 learner corpora, and lingua franca corpora. It also discusses application of the corpus approach, including indirect applications and direct applications. In a final section, it presents some caveats of the corpus approach for future language teaching research.